The process of margondang in the traditional batak angkola wedding ceremony: semiotics studies - Siregar, S.S. Pertiwi K.A.W.; Mayasari, Mayasari; Zuindra, Zuindra (Gema Wiralodra, 2023)
The purpose of this research is to provide understanding to the readers and increase their knowledge about the Margondang process in Batak Angkola wedding, so that they can easily understand it. Researchers analyzed using the theory of Ferdinand De Saussure (1857). The analysis in this study uses qualitative research methods. To support the analysis, researchers used books, journals and theses. Researchers obtained the data from videos and photos. The result search that the process of the Margondang ceremony in the Batak Angkola wedding goes through three stages and each of the traditional events carried out contains moral values.